EFEKTIVITAS PENGGUNAAN FLASHCARD BERBASIS AUGMENTED REALITY MATERI EKOSISTEM TERHADAP LITERASI SAINS KELAS 5 SDN BENDO 01 PONGGOK BLITAR - Muji Rahayu Santi Sumarah; Shofi Nur Amalia; Ragil Tri Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effectiveness of augmented reality-based flashcard media on ecosystem material. And to determine the increase in science literacy of grade 5 students of SDN Bendo 01 Ponggok Blitar. This study used an experimental method in the form of a quasi-experimental design. The population in this study were 40 grade 5 students of SDN Bendo 01 Ponggok Blitar with the number of students in class 5A 20 students and class 5B 20 students. Data collection techniques in this study used tests and documentation. The results of the normality test of the experimental class in this study were 0.016> 0.05 in the pretest data and the significant value of the posttest was 0.092> 0.05 normally distributed. The results of the homogeneity test can be seen that the significant value of the posttest data is 0.100, this indicates that the value of the significant 0.100> 0.05 so that the posttest data criteria accept H0 which means that both classes have homogeneous variance. The results of the independent sample t-test on the posttest data of the experimental class and the control class can be seen that the sig. (Two-Sided p) value is 0.002 <0.05. The results of the paired sample t-test on the pretest and posttest data using SPSS 30.0 can be seen that the sig. (Two Side p) value is 0.001 <0.05, so there is a significant difference between the pretest and posttest. The improvement of the science literacy skills of grade 5 students of SDN Bendo 01 Ponggok Blitar was obtained from the pretest and posttest assessments.